Relationship Between Internationalization and Eco-Innovation Strategies: a Brazilian chemical industry study - Maçaneiro, Marlete Beatriz; Battisti, Patrícia Stafusa Sala; Vigorena, Débora Andrea Liessem; Steiner Neto, Pedro José; Cunha, Sieglinde Kindl da (Desenvolvimento em Questão, 2019)
This study investigates the association of contextual factors with the adoption of eco-innovation strategies, between internationalized and non-internationalized companies. As part of the research, there is an analyses of the average values for the adoption of contextual factors and eco-innovation strategies between these group of companies. The quantitative research method was used by performing a cross-sectional survey in 124 Brazilian chemicals manufacturing companies. The results from the analysis of the surveys show within the non-internationalized companies there is a better association between the contextual factors of top management support, technological competence, environmental standards and proactive eco-innovation strategies. Results also reveal that internationalized companies do not differ from the other companies regarding to the adoption of environmental regulatory factors, reputation effects, top management support, reactive strategies and proactive strategies. In conclusion, this study indicates that the Brazilian surveyed companies are concerned about eco-innovation, regardless of their status and scope within their market.